Perkin-Elmer infrared spectroscopy equipment in use at Broome Community College laboratory - Perkin-Elmer Corporation (1970)
General view of two unidentified students operating Perkin-Elmer infrared spectroscopy equipment in the chemical analysis instrument laboratory at Broome Community College in New York State. Per notations accompanying the photograph, the laboratory is used to train students for careers as laboratory technicians or for higher studies in analytical instrumentation.
Keywords: Women in science; Perkin-Elmer Corporation; Laboratory technicians--Training of; Scientific apparatus and instruments; Women college students; Infrared spectroscopy; Corporations; Broome Community College; Students; Laboratories; College students